1989
DOI: 10.1093/jnci/81.20.1571
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, Pregnancy, and Risk of Breast Cancer

Abstract: We investigated the relationship between hypertension and breast cancer using data from a large case-control study of women younger than 55 years. Among nulliparous women, there was little evidence of an association between hypertension and breast cancer. Among parous women, hypertension reduced the risk of breast cancer if it had been diagnosed at any time in their lives before the end of the most recent pregnancy (odds ratio = 0.73; 95% confidence interval = 0.59-0.92). Several earlier studies indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Previous studies have also shown an inverse association related to pre-eclampsia (Polednak and Janerich, 1983;Thompson et al, 1989;Troisi et al, 1998;Cohn et al, 2001;Vatten et al, 2002a, b), but no previous study has assessed whether the offspring's gender could modify this association.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also shown an inverse association related to pre-eclampsia (Polednak and Janerich, 1983;Thompson et al, 1989;Troisi et al, 1998;Cohn et al, 2001;Vatten et al, 2002a, b), but no previous study has assessed whether the offspring's gender could modify this association.…”
Section: Discussionmentioning
confidence: 98%
“…Women who are diagnosed with pre-eclampsia in pregnancy may have a lower risk for breast cancer later in life compared to other parous women (Polednak and Janerich, 1983;Thompson et al, 1989;Troisi et al, 1998;Cohn et al, 2001;Vatten et al, 2002a, b) although a higher risk has also been reported (Paltiel et al, 2004). Women who develop pre-eclampsia tend to have higher levels of androgens and lower oestrogen and progesterone levels than women in normotensive pregnancies (Innes and Byers, 1999).…”
mentioning
confidence: 96%
“…13 Several studies have observed an inverse association between pre-eclampsia and subsequent maternal risk of breast cancer. 14 Also, gender of offspring may influence the risk of developing breast cancer. A recent study observed that breast cancer risk at young age was significantly lower in women who gave birth to 2 or more boys, but no girls, compared with women who gave birth to 2 or more girls, but no boys.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of an effect on maternal risk is perhaps best for preeclampsia where breast cancer risk is lower in women who experienced preeclampsia or hypertension during pregnancy in most (64,(169)(170)(171)(172), but not all studies (173,174). Moreover, data from the Child Health and Development Studies show a marked reduction in breast cancer risk with elevated mean arterial pressure (175), and systolic blood pressure increases from mid-to late pregnancy below the diagnostic criterion for hypertension (58).…”
Section: Prenatal Risk Factors For Maternal Breast Cancermentioning
confidence: 99%